The effects of Korean country-of-origin on Mongolian consumer product evaluation and purchase intention - Sharmuud Haliun; Seong Do Cho (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2015)
The economy of Mongolia has been growing, especially due to imports growing more than exports. The purpose of this study is to examine the impact of a Korean country-of-origin on Mongolian consumer product evaluation and purchase intention using a Korean laptop. Specifically, this study tested the independent and moderating roles of human values and socio-psychological variables in the relationships between country-of-origin, product evaluation, and purchase intention. The survey was conducted with 143 young respondents in Mongolia. The results of this study indicate that Korean country-of-origin positively affects Mongolian consumer product evaluation and purchase intention. Second, because the human value of power is tied into consumers' social status and positions, Mongolian consumers with more power had weaker purchase intention for Korean country-of-origin products. However, findings show that the international social network moderates effects of Korean country-of-origin in product evaluation. In other words, Mongolian consumers with connections to international people tend to positively evaluate products imported from developed Asian countries.
Keywords: M00; M1; M3; F00; F2; F6; 650; Country-of-origin; Mongolian consumer; human value; international social network